Occurrence of different aphid species in the tomato of avelar, State of Rio de Janeiro, Brazil - Oliveira, Alda Maria de; Sulo, Shinobu; Barcellos, Deosdedes Francisco (Pesquisa Agropecuaria Brasileira, 2014)
Observations were made concerning the occurrence of the aphid population in Avelar, State of Rio de Janeiro, from September 1971 to August 1972. Of the aphid population sampled, 50.49% were Myzus persicae (Sulz,), 25.52% were Aphis gossypii Glover, 11.00% were Macrosiphum rosae (L.), 4.18% were Brevicoryne brassicae (L.) and 8.81% were other species. The authors found an infestation index for "yellow top" virus of about 70% of the tomato crop in this area. Myzus persicae (Sulz.) is considered to be the major transmitter of this disease.